Evolution of a dark vortex on Neptune with transient secondary features - Wong, MH; Sromovsky, L; Fry, P; Sánchez-Lavega, A; Hueso, R; Legarreta, J; Simon, AA; Morales-Juberías, R; Tollefson, J; de Pater, I; Irwin, PG (Elsevier, 2022)
Dark spots on Neptune observed by Voyager and the Hubble Space Telescope are thought to be anticyclones with lifetimes of a few years, in contrast with very long-lived anticyclones in Jupiter and Saturn. The full life cycle of any Neptune dark spot has not been captured due to limited temporal coverage, but our Hubble observations of a recent feature, NDS-2018, provide the most complete long-term observational history of any dark vortex on Neptune. Past observations suggest some dark spots meet their demise by fading and dissipating without migrating meridionally. On the other hand, simulations predict a second pathway with equatorward migration and disruption. Our HST observations suggest NDS-2018 is following the second pathway.